1. dx/y+z = dy/-(x+z) = dz/x-y
We solve it y Lagrange's multipliers method
"\\frac{(ldx+mdy+ndz)}{(lP+mQ+nR)}=0\\\\\nlP+mQ+nR=0\\\\"
So,
"ldx+mdy+ndz=0"
Here "l,m,n" are multipliers
"\\frac{dx}{y+z}=\\frac{dy}{-x-z}=\\frac{dz}{x-y}," given.
So,
"1dx+1dy+1dz=0"
Since
"1(y+z)+1(-x-z)+1(x-y)=0,"
"1,1,1" are multipliers
And
"x(y+z)+y(-x-z)+z(x-y)=0,"
So "x,y,z" are multipliers
"\\therefore 1dx+1dy+1dz=0"
After integration
"x+y+z=C_1---------(i)"
Also "xdx+ydy+zdz=0"
After integration
"x^2+y^2+z^2=C_2---------(ii)"
"(i)" and "(ii)" are the required solutions
2.(x^2D^2-3xD+5)y =x^2(logx)
Let "x=e^z" and "ln x=z"
"\\implies \\frac{dx}{dz}=e^z=x\\\\\n\\implies \\frac{dz}{dx}=\\frac{1}{x}"
Now,
"\\frac{dy}{dx}=\\frac{dy}{dz} \\cdot \\frac{dz}{dx} = \\frac{dy}{dz} \\cdot \\frac{1}{x}\\\\\n\nx \\frac{dy}{dx} = \\frac{dy}{dz}\\\\\nif\\ \\frac{d}{dz} \\equiv \\theta, then\\\\\nxDy= \\theta y"
Similarly,
"x^2D^2y=\\theta(\\theta - 1) y"
Now,
"(\\theta ^2 - \\theta - 3\\theta+5)y=ze^{2z}\\\\\n\\implies (\\theta ^2 - 4\\theta+5)y=ze^{2z}"
This is a non homogeneous differential equation of the second order.
The remaining solution should be elementary.
The characteristic equation "r^2-4r+5" has the solutions "r=2-i, 2+i" . While the particular solution (by the method of undetermined coefficients) comes out to be "Y_p=e^{2z}"
Then the general solution (in terms of "z" ) is given by,
"y=y_c+y_p=C_1e^{z(2+i)}+C_2e^{z(2-i)}+e^{2z}"for arbitrary constants "C_1" and "C_2."
"y=C_1x^{(2+i)}+C_2x^{(2-i)}+x^{2}"
Comments
Leave a comment